Early prediction of feed intolerance in very low birth weight preterm infants using superior mesenteric artery blood flow velocity. (1st December 2020) - Jain, Nidhi; Ramji, Siddarth; Jain, Ashish; Modi, Manoj; Sharma, Pradeep
Abstract: Objective: To evaluate the utility of superior mesenteric artery (SMA) flow velocity post feeding for predicting time to achieve full enteral feeds in very low birth weight (VLBW) neonates. Subjects: In this prospective cohort study preterm VLBW infants were followed until they achieved full enteral feeding. Results: There was no significant difference between prefeed and post feed SMA flow measurements in study subjects. At baseline, it was observed that Small for gestational age (SGA) babies had a significantly lower peak systolic velocity. Time-averaged mean velocity (TAMV) was significantly lower in SGA babies at baseline, 15, 30, 45, and 60 min post feed, but there were no within-group differences noted over time. Conclusion: SMA blood flow velocity measured pre-feed and post-feed times do not correlate with the time to achieve full enteral feeding in very low birth weight neonates. The clinical significance of lower Peak systolic velocity (PSV) and TAMV in SGA infants is unclear.